PERANCANGAN APLIKASI SISTEM INFORMASI PELATIHAN KARYAWAN BERBASIS WEBSITE PADA PT. XYZ - Handa Gustiawan; Hesti Rian (JURNAL LENTERA ICT, 2025)
This research was conducted to develop a web-based employee training information system application at PT XYZ to improve the efficiency and effectiveness of the training process. This system is designed to assist in managing training schedules, materials, and participant data, as well as providing flexible learning access for employees. Testing results indicate that the system operates well and meets user needs. It is hoped that this application can provide a solution to support the sustainable development of employee competencies.